PERFORMANCE OF WASTE RESIDUAL PELLETIZED BIOMASS SOLID FUEL FROM MIXTURE OF COW DUNG AND PALM OIL FIBRE - KHOR, JIE SHENG (IRC, 2018)
This report presents an investigation on the potential of biomass feed stock pelletizing from the waste residual performance between cow dung and palm fibre. Due to their homogeneous size, pelletizing has been a clear trend in the production of biomass energy as it improved the handling and feeding process. In this report, pelletizing of agricultural waste which are cow dung and palm fibre is introduced with the objective to study the chemical composition of cow dung and palm fibre. Besides that, the durability of the pellet is tested on the samples. The performance of pellet is also analyzed in determining the best combination ratio between cow dung and palm fibre. The current trend of biomass, chemical composition of cow dung and palm fibre, mechanism of pelletizing and test analysis are studied in this report. The methodology of this research started with the collection of agriculture residue, followed by drying and pelletizing. Calorific value and percentage weight loss were measured through Bomb Calorimeter Test and Thermogravimetric Analysis (TGA). The results suggest that the pellet content of 50 % cow dung and 50% palm fibre is the most suitable as it has high calorific value and has great strength and handling. The requirement of biomass pelletizing and pellet performance are explained in this study.